The dogmatism of the contemporary “legal” self-determination: The right of self-determination as a juridical and philosophical issue - di Marco, Rudi (Derecho Público Iberoamericano, 2020)
The essay deals with delicate and controversial juridical issue, powerfully drawn to the attention of all jurists and been subject of Costitutional Courts’ and CEDU’s jurisprudence. The subject’s self-determination is an essential condition of law, but it is also a condition of subjective sovereignty’s claim representing the basis of “new rights” (euthanasia, consensual homicide...). The reflections developed in the text reveal the contraddiction inside of modern self-determination theory. This “new right”, infact, is presented as a human right and it is defended as a form of negative-freedom, but this kind of self-determination transform every individual freedom in legal freedom, id est in a form of freedom limited by positive law.